Optimizing Interactive Flipbooks as a Literacy Learning Media in Elementary School - Khusnul Fatonah; Ahmad Muzaki (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to optimize the use of interactive flipbooks as a literacy learning media in elementary schools. Interactive flipbook media offers an innovative approach in the learning process, combining engaging visualization, interactivity, and digital accessibility that meets the needs of 21st-century students. The method used in this research is a literature review involving the collection, analysis, and synthesis of various literature related to the use of interactive flipbooks in the context of primary education. The results indicate that interactive flipbooks can enhance reading interest, literacy skills, and student comprehension through a combination of text, images, audio, and animation. This media also allows students to learn independently and collaboratively by utilizing interactive features. In addition, interactive flipbooks have proven effective in supporting thematic and integrative learning, which is often implemented in elementary schools. This study recommends the development of curriculum-based interactive flipbooks, teacher training in their use, and the integration of this media into teaching strategies. With proper optimization, interactive flipbooks can become an innovative solution to improve the literacy quality of elementary school students.